The Effectiveness of Using Role Play Method in Enhancing English Speaking Skills of Junior High School Students - Kinza Adiguna Darmawan (Institute of Accounting Research and Novation (IARN), 2024)
This research aims to examine the effectiveness of the role play method in enhancing English language learning, particularly speaking skills, among junior high school students. The study was conducted using a quasi-experimental design involving two groups: an experimental group taught using the role play method and a control group taught through conventional methods. Data were collected through pre-tests and post-tests, classroom observations, and student questionnaires. The results showed that the experimental group demonstrated significant improvement in their speaking abilities, including fluency, vocabulary, pronunciation, and confidence, compared to the control group. Additionally, classroom observations revealed higher levels of student engagement, participation, and enthusiasm during role play sessions. Feedback from students also indicated that they found role play to be an enjoyable and effective way to practice English in meaningful, real-life contexts. The findings support the use of role play as a student-centered teaching method that not only improves language competence but also encourages active learning and reduces anxiety in the language classroom. This research contributes to the growing body of literature supporting communicative and experiential approaches in English language teaching and recommends that educators incorporate role play into their teaching practices to enhance student outcomes in English learning.